MENGGALANG SEMANGAT JIWA BERWIRAUSAHA DI KALANGAN MAHASISWA DAN MENINGKATKAN SEKTOR UMKM MELALUI PROGRAM WIRAUSAHA MERDEKA EDUBLANK ON UNIVERSITAS NEGERI YOGYAKARTA - Asmanto, Budi; Sila Chandra, Yolandika; Widodo, Suyud (Jurnal Ilmiah Sistem Informasi (JISI), 2024)
The research evaluates the effectiveness of the "Wirausaha Merdeka" Program in fostering entrepreneurial spirit among students and enhancing the quality of Micro, Small, and Medium Enterprises (MSMEs). Focused on the Immersion phase, particularly the internship activities within MSMEs, it aims to elevate student comprehension and motivation in entrepreneurship. The primary objective is to gauge the program's success in fostering entrepreneurial zeal among students and its impact on MSMEs. It's an evaluative qualitative study of the "Wirausaha Merdeka Edu blank On" Program at Yogyakarta State University. Involving conceptual understanding, practices, evaluations, and internship experiences, the research, conducted by a participant, utilizes qualitative data analysis to illustrate successes and challenges in instilling entrepreneurial spirit. The "Wirausaha Merdeka" Program effectively cultivates entrepreneurial spirit among students and MSMEs. Students exhibit improved entrepreneurial skills such as time management, communication, and innovative job creation The program's positive impact is evident in the economic contributions resulting from student ventures. It successfully encourages entrepreneurial drive, innovation, and employment opportunities for students